Densification behaviour and properties of manganese oxide doped Y-TZP ceramics - Ramesh, Singh; Amiriyan, M.; Meenaloshini, S.; Tolouei, R.; Hamdi, M.; Pruboloksono, J.; Teng, W.D. (Elsevier, 2011)
The effect of employing a short sintering holding time of 12 min as compared to that of the commonly employed holding time of 120 min (2h) on the properties of undoped and I wt manganese oxide (MnO(2))-doped Y-TZP ceramics were studied. Sintering studies was conducted over the temperature range of 1150-1600 degrees C. Bulk density, Young's modulus, Vickers hardness and fracture toughness tests were carried out on the sintered samples. The results revealed that the 12 min sintering holding time was effective in promoting densification of the 1 wt MnO(2)-doped Y-TZP without sacrificing tetragonal phase stability or mechanical properties and incurring grain growth. Microstructure investigation by using the scanning electron microscope (SEM) of the fracture MnO(2)-doped Y-TZP samples which was subjected to rapid quenching in liquid nitrogen revealed distinct microstructural features believed to be associated with the presences of a transient liquid phase during sintering. A sintering mechanism was subsequently proposed to explain the densification behaviour of MnO(2)-doped Y-TZP ceramics. (C) 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved.